KEEFEKTIFAN PENGGUNAAN MEDIA VIDEO ANIMASI IPA SD BERBASIS LITERASI SAINS TERHADAP HASIL BELAJAR SISWA KELAS IV - Wulandari, Mey Prihandani (JURNAL PANCAR (Pendidik Anak Cerdas dan Pintar), 2019)
The purpose of this study was to determine the effectiveness of the use of science video animation media based on science literacy on the learning outcomes of fourth grade students. This research is an experimental research design with True Experimental Design, the form of research used is Posttest Only Design. The subjects of this study were students at SD Negeri 1 Jatilawang, Class IV A and Class IV B. Where Class IV B was an experimental class (using animation literacy-based video media) and class IV A as a control class (using conventional media), which then measurements taken. Based on the results of the study, it can be concluded that the use of video animation media based on scientific literacy is effective in improving student learning outcomes at SD Negeri 1 Jatilawang. Based on hypothesis test with used two-sample t-test, generated p-Value = 0,126. Because p-Value > ? = 0,05, then H0 is rejected or Ha is accepted, meaning the use of science video animation media based on science literacy is effective in improving student learning outcomes of grade IV at SD Negeri 1 Jatilawang. While based on the results of N-gain calculations to find out how much the increase in student learning outcomes before and after being given treatment, generated gain of experimental class = 0.512 and gain of control class = 0.364, so it can be concluded that the increase in learning outcomes in the experimental class is higher than the control class.